Improving the Quality of Digital Images Using the Image Averaging Method - Upa Yuandari (The IJICS (International Journal of Informatics and Computer Science), 2020)
Image is a representation (picture), similarity, or imitation of an object. The use of digital images plays an important role as a form of information due to its advantages. Although it is rich in information, not all images have a good visual appearance. This can be due to interference in the form of noise, color intensity that is too contrasting or blurred. Noise itself is a disturbance caused by distorted digital data received by the image data receiver, starting from the movement during shooting by optical devices such as cameras, the use of optical devices that are not in focus, short lighting thereby reducing the number of photos captured by optical devices, or the weather when shooting. Noise can be removed by using the Image Averaging Method